Question Answering with Knowledge Base, Web and Beyond - Yih, Scott Wen-tau; Ma, Hao (Proceedings of the 39th International ACM SIGIR Conference on Research and Development in Information Retrieval, 2016)
In this tutorial, we give the audience a coherent overview of the research of question answering (QA). We ﬁrst introduce a variety of QA problems proposed by pioneer researchers and brieﬂy describe the early eﬀorts. By contrasting with the current research trend in this domain, the audience can easily comprehend what technical problems remain challenging and what the main breakthroughs and opportunities are during the past half century. For the rest of the tutorial, we select three categories of the QA problems that have recently attracted a great deal of attention in the research community, and present the tasks with the latest technical survey. We conclude the tutorial by discussing the new opportunities and future directions of QA research.